Deviasi Seksual Dalam Perspektif Psikologi Islam (Solusi Atas Masalah Deviasi Seksual Dalam Psikologi dan Al-Qur’an) - Ihsan, Muhammad; R, Rahmadani; Shofiah, Vivik; Rajab, Khairunnas (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Social deviation is social behavior that is not based on the rules that apply in society. Social deviation or deviant behavior can occur anywhere, both in the family and in the community. One of the social deviations that often occurs among us is sexual deviation. The basis for this idea stems from the high level of deviant sexual behavior in society which is increasingly worrying. For example, free sex, living together, homosexuality, lesbianism and various other sexual deviations that we often encounter and hear about in our society. The existence of the digital world is a breath of fresh air for those who are looking for fake sexual satisfaction. From an Islamic perspective, this sexual deviation is clearly contrary to the creation of humans by Allah SWT. Based on existing phenomena, the author wants to discuss how the issue of sexual deviation is understood from psychology and the Koran. The method used in this research is library research where the source of information for this research is references to the Al-Quran manuscripts, books about sexual deviation, and journal articles that are appropriate to the phenomenon presented.